THE ESTABLISHMENT OF SURKHANDARYA REGION AND THE FORMATION OF THE PUBLIC EDUCATION ADMINISTRATIVE SYSTEM A HISTORICAL ANALYSIS (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article examines the establishment of Surkhandarya region as a separate administrative unit within the Uzbek SSR on 6 March 1941 and the concurrent formation of the public education administrative system in the region. Drawing on archival evidence and existing scholarly literature, the study reconstructs the institutional and pedagogical context in which the regional educational apparatus took shape during the brief pre-war period — a period that lasted only three and a half months before the outbreak of the Great Patriotic War on 22 June 1941. The article analyses three interrelated dimensions: (1) the administrative and territorial preconditions for the formation of the region, including the transition from the okrug (district) system of the 1920s through the period when southern districts were directly subordinated to the republican centre; (2) the structural organisation of the three-tier educational management system (Republican Commissariat of Education — Regional Education Department [oblono] — District Education Department [rayono]); and (3) the initial pedagogical infrastructure of the region, including the Termez Pedagogical College as the principal source of teaching personnel.
Keywords: Surkhandarya region; Uzbek SSR; public education; educational administration; regional history; Termez Pedagogical College; Soviet education policy; pre-war period; Central Asia.